Concomitant tumor resistance - Chiarella, Paula (2012)
Concomitant tumor resistance (CR) is a phenomenon in which a tumor-bearing host is resistant to the growth of secondary tumor implants. This phenomenon has been described in human and animal systems and it can be generated by both immunogenic and non-immunogenic tumors. The relevance of CR to the mechanisms of metastases control has been highlighted by numerous observations showing that the removal of human and murine tumors may be followed by an abrupt increase in metastatic growth, suggesting that a primary tumor may exert a controlling action on its metastases which could be considered as secondary tumor implants developed spontaneously during the primary tumor growth. A more profound understanding of the different mechanisms claimed to be associated with the phenomenon of CR could contribute to develop new and more harmless means to manage malignant diseases, especially by limiting the development of metastases that arise after resection of primary tumors or after other stressors that may promote the escape of metastases from dormancy.